Food bags, silent squares: Changes in the actions of state agents and social activists in Buenos Aires - Sofia Silva; María Fernanda Alonso; Stella Maris García (Íconos)
The sanitary measure of social isolation – preventive and obligatory, decreed by the Argentine State due to the pandemic caused by COVID-19, brought about changes in the ways of operating of state agents and those who work in Indigenous and migrant organizations. This article analyzes the changes in the circumstances imposed by the new context, the displacements and pauses that occurred in the Provincial Council of Indigenous Affairs of the Province of Buenos Aires, and the work of an intermediary engaged in social activism with civil associations of migrants in Greater La Plata. In order to document these changes, the text is based on an ethnography, based on observations and interviews, and on the analysis of documents found in state offices and digital platforms. As a result of fieldwork, interdependencies and tensions between redistributive and recognition public policies aimed at migrant and Indigenous organizations have been identified. We observed that strategies and policies aimed at recognition were attenuated by the need to respond to the pressing health situation and the impossibility of accessing public space during the pandemic.